Economic efficiency of early magnetic resonance imaging (MRI) in intra-knee injuries: reduction of recovery time and reduction of late rehabilitation costs - Gaybullaev Sherzod Obid ugli; Khamidov Obid Abdurakhmаnovich (THE INNOVATION ECONOMY, 2026)
This article assesses the clinical and economic effectiveness of the use of early magnetic resonance imaging (MRI) in internal injuries of the knee joint. The possibility of early accurate diagnosis using MRI, the correct and timely appointment of treatment, and reducing the duration and costs of rehabilitation was investigated. Functional results, recovery time, and overall medical costs were compared between two groups: patients who underwent early MRI and those diagnosed with delay. The obtained results indicate the high effectiveness of early MRI.